Kyrgyz of Uzbekistan (Ferghana valley), their localization and tribal composition. End of the XX century (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The scientific article examines data on Kyrgyz living outside the territory of Kyrgyzstan, in the Republic of Uzbekistan. The article examines their localization, areas of distribution and settlement of the Kyrgyz in the Fergana Valley, tribal composition, material and spiritual culture. The Fergana Valley, which is currently under the jurisdiction of independent states (Kyrgyzstan, Uzbekistan, Tajikistan), has been known since ancient times under the additional name “Golden Valley”. The history, culture, language of the Kyrgyz and Kyrgyz ethnic group and other features are closely related to the population and culture of the Fergana Valley. It is known that the Kyrgyz have lived in the valley, its foothills and mountainous areas since time immemorial. Some historical sources and works of researchers indicate that the Kyrgyz inhabited the Fergana Valley and surrounding areas in the 10th-11th centuries. AD It should be noted that the Kyrgyz have long lived in the Fergana Valley and its foothills. An example of this, along with historical sources, can be toponymic names associated with the names (ethnotoponyms) of Kyrgyz tribes and clans, which are quite densely populated in the region.In general, to date, comprehensive studies of the ethnic history, ethnogenesis, ethnic culture, language, material and spiritual culture of the Kyrgyz living in Uzbekistan have not been carried out. For the analysis, scientific, scientific and statistical materials on the number and settlement of the Kyrgyz in the Fergana Valley were used. The ethnocultural ties of the Kyrgyz people with other Turkic-speaking peoples have also been studied.
Keywords: Kyrgyz, Fergana Valley, statistics, Soviet power, Kyrgyz tribes, ethnicity, right wing, left wing, Bulgachi (ichkiliks)